SPIRITUAL PSYCHOLOGY OF THE CHARACTER (on the example of the works of Kuchkar Narkobil) (Scientific journal of the Fergana State University, 2023)
The article examines the issues of psychology in the psyche of the characters in the stories of K. Norkobila. He examines the stories "Mystery Under the Sky" and "Invasion".